The impacts of the COVID-19 pandemic on the mental health of students (Research, Society and Development, 2021)
Aim: To demonstrate statistics related to the impacts of the pandemic on students' mental health. Methods: This is an integrative review carried out in July 2021, on LILACS, SciELO and Pubmed platforms via MEDLINE. Articles published in 2020 and 2021 were selected, in Portuguese, English, Spanish, French, and excluded theses, dissertations, editorial, letter to the editor, opinions and literature reviews. Results: It was found 202 articles and after the appraisal it was selected 10 articles, it was possible to evidence the increase of negative psychological manifestations in higher education students during the COVID-19 pandemic. Final considerations: It was found that most higher education students may report mental illnesses that may be related to the lack of social interaction in the face of social distance. Given the above, this study sought to contribute to data recognition and to soon serve health organizations with measures and solutions to reduce cases of university students with mental problems.